EVALUASI PENGGUNAAN ANTIBIOTIK PADA BALITA PENDERITA PNEUMONIA RAWAT INAP DI RSUD â€œYâ€ DI KOTA â€œXâ€ TAHUN 2016 - 'Utsman, Panji; Karuniawati, Hidayah (Pharmacon: Jurnal Farmasi Indonesia, 2020)
Pneumonia was pulmonary lung disease called parenchyma caused by microorganism, Pneumonia can be cured byantibiotic to prevent the resistantof bacteria and to improve the effective of the treatment, the right antibiotic must be determining. This research purpose is to determine the accuracy of using antibiotic in toddler patients suffering pneumonia who hospitalized in RSUD ?Y? ?X? City, in 2016. This is nonexperimental research. Data collected retrospectively and was analized descriptively. Samplestaken by purposive sampling method which searched the medical report of toddler patient suffer pneumonia hospitalized in RSUD ?Y?X City, in 2016 which met the inclusion criteria. Reseach accuracy was analized used ?Pedoman Pelayanan Medis Ikatan Dokter Anak Indonesia year 2009? and ?British National Formularium for Children 2011-2012?, Such as indication accuracy, precision medicine accuracy, patient accuracy and drug dose accuracy. The result of the research was found that in 49 toddler patient suffering pneumonia, the kind of antibiotic used was cefotaxime (89,80%), Ampicillin (4,08%), combination of cefotaxime + gentamicin (4,08%) and ampicillin + gentamicin (2,04%). Evaluation of accuracy of the use antibiotic 100% right in indication, precision medicine by 93,87%,100% patient accuracy, and 10,20% drug dose accuracy.